Topological aspects of dynamical systems on manifolds - Sharko, V.V. (Український математичний журнал, 1993)
The necessary and sufficient conditions for existence on manifolds of the dynamical systems having non-wandering set consisting of disconnected union of 2-dimensional tori with hyperbolic structure are given